Antibodies to Senescent Antigen and C3 Are Not Required for Normal Red Blood Cell Lifespan in a Murine Model - Hudson, Krystalyn E.; de Wolski, Karen; Kapp, Linda M.; Richards, Amanda L.; Schniederjan, Matthew J.; Zimring, James C. (Frontiers in Immunology, 2017)
Red Blood Cells (RBCs) have a well-defined lifespan, indicating a mechanism by which senescent cells of a certain age are removed from circulation. However, the specifics by which senescent cells are recognized and removed are poorly understood. There are multiple competing hypotheses for this process, perhaps the most commonly cited is that senescent RBCs expose neoantigens (or senescent antigen(s)) that are then recognized by naturally occurring antibodies, which opsonize the senescent cells and result in clearance from circulation. While there are a large volume of published data to indicate that older RBCs accumulate increased levels of antibody on their surface, to the best of our knowledge, the causal role of such antibodies in clearance has not been rigorously assessed. In the current report we demonstrate that RBC lifespan and clearance patterns are not altered in mice deficient in antibodies, in C3 protein, or missing both. These data demonstrate that neither antibody nor C3 is required for clearance of senescent RBCs, and questions if they are even involved, in a murine model of RBC lifespan.